Clarification on Classical Fatigue Design for Biaxial Stress Fields - Paulo M. S. T. de Castro (Designs)
Fatigue design is a compulsory topic in education for several engineering specialties, particularly mechanical engineering. Textbooks on the design of machine elements have included, since long ago, the treatment of high-cycle fatigue (HCF) according to a classical theory based on the pioneering work of many researchers such as Carl Richard Soderberg. Perusing textbooks published over a long period, as well as comparing current ones, leads to the conclusion that the classical approach is presented with some differences in many of these textbooks, and this raises the need for some clarification: what are the consequences of the differences found? The present technical note addresses this problem, starting by presenting the classical approach, emphasising the variations in presentation identified, and then making a systematic comparison in order to grade the conservatism of the several variants found.